PREVALENCE AND PATTERN OF SEVERE MALARIA AMONG CHILDREN IN TWO GENERAL HOSPITALS, JIGAWA STATE- NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
The prevalence and pattern of presentation of severe malaria differ from one area to another, in one age group and gender. A descriptive cross sectional study of children between the ages of one month and fourteen years with symptoms of severe malaria was conducted between July and December 2018 in Dutse and Birnin Kudu Local Government Area of Jigawa State. Venous blood samples were used for parasitological, hematological and biochemical examination following standard procedures. Thick and thin blood films were prepared, stained and examined at x100 magnification. A total of 172 children were considered in which, 73/167(43.7) children had severe malaria. Children less than 5 years of age had the highest percentage of severe malaria (47.1%; 95% CI = 39.5 to 54.7). Hyperpyrexia, prostration, hyper parasitemia and multiple convulsions were the commonest presentations. While metabolic acidosis, jaundice, hypoglycemia and respiratory distress were the least presenting features, no child presented spontaneous bleeding or shock. Furthermore, 21/73 children with severe malaria had only one feature of severity, 32/73 (43.8) had two features of severity, while 14/73 (19.2) of the children had up to three features. Only 4/73 (5.5) children had four of the features of severity. Chi-square analysis showed significant difference (P
Keywords: Cerebral malaria, Children, Plasmodium falciparum, Prevalence, Severe Malaria